EXTRACTION OF PAPRIKA OLORRESINAS (CAPSICUM ANNUM L.) IN UNIT PILOT - Bautista C., Mario (2008)
In this work oleorresin of páprika (Capsicum annum L.), was obtained, using a Pilot Extraction Unit. As a resoult viscous and oily oleorresin was produce with a 1980 ASTA color , considered satisfactory in the market.